Demonstrating Higher Incidence of Advanced Breast Malignancies in Our Young Hispanic Population. Issue 11 (November 2018) - Klein, Amanda; Villareal, Michael; Radpour, Sepeadeh; Goodgame, Boone; Ali, Sadia; Clark, Adam; Uecker, John
Historically, the Hispanic population in the United States has had a lower incidence of cancer than the matched non-Hispanic population, despite disparities in access to health care, screening, and prevention. Our experience in Austin, Texas, directly contradicts this. We have seen a disproportionate amount of young Hispanic patients with advanced malignancies, particularly of the breast. The aim of this study was to compare the incidence of advanced breast malignancies. We performed a retrospective review over a 10-year period (2003–2013) of all newly diagnosed breast cancer patients. Data were collected from the cancer registry. Patients were divided into two groups: Hispanic versus non-Hispanic descent, with a subgroup of those aged less than 50 years. Primary outcome was the incidence of advanced cancers (stage 3 or 4). There were a total of 3968 breast cancer patients seen in our Shivers Cancer Center from 2003 to 2013, with an overall incidence of advanced breast cancer of 11.5 per cent. Of the patients aged less than 50 years, 14.2 per cent had advanced breast cancer. However, the rate among Hispanic patients was 21.3 per cent, whereas in non-Hispanic patients it was 13.5 per cent, P = 0.002. Being Hispanic was found to be an independent predictor of having advanced malignancies at a young age (odds ratio 1.7, confidence interval 1.1–2.5, P = 0.01). Here in Austin, Texas, we have found a higher overall incidence of breast cancer among young Hispanic women. This is important to recognize because more efforts may be required to increase screening and health-care access to this population.